Β-Sitosterol of Red Dragon Fruit (Hylocereus Polyrhizus) and Its Response to Macrophage And Nitric Oxide - Sri wahdaningsih (Universitas Gadjah Mada, 2021)
Hylocerius polyrhizus has relatively big potency as natural antioxidant. The compound considered as antioxidant also has immunomodulatory activity. This study showed isolation for identifying the active compounds in H. polyrhizus peels that are able to increase immune system of human body. The methanol extracts were partitioned and fractionated. The active compounds of petroleum ether fraction were partitioned and purified using Preparative Thin Layer Chromatography (PTLC). The identification of active compound structures was done with spectroscopy: UV, FT-IR, 13CNMR, 1HNMR, DEPT and HSQC. The immunomodulatory activity was also tested. Based on the spectroscopic data, the identified isolate was β-sitosterol. The statistical analysis of macrophage cell activity and nitric oxide showed that isolates at the highest concentrations of 100 µg/mL were able to activate macrophage cells and enhance the production of nitric oxide.